Somebody everybody listens to - Supplee, Suzanne (New York : Dutton, 2010)
Upon graduating from high school in the tiny town of Starling, Tennessee, aspiring country singer Retta Lee Jones manages to get herself to Nashville, where, in spite of some bad luck and hard times, she tries to persevere in pursuing her dreams.
"A novel"--Cover.
Keywords: Singers -- Juvenile fiction; Country life -- Tennessee -- Juvenile fiction; Self-confidence -- Juvenile fiction; Country music -- Juvenile fiction; Singers -- Fiction; Country life -- Tennessee -- Fiction; Self-confidence -- Fiction; Country music -- Fiction; Nashville (Tenn.) -- Juvenile fiction; Nashville (Tenn.) -- Fiction